A systematic review of the impact of stroke on social support and social networks: associated factors and patterns of change. (August 2016) - Northcott, Sarah; Moss, Becky; Harrison, Kirsty; Hilari, Katerina
Objective: Identify what factors are associated with functional social support and social network post stroke; explore stroke survivors' perspectives on what changes occur and how they are perceived. Data sources: The following electronic databases were systematically searched up to May 2015: Academic Search Complete; CINAHL Plus; E-journals; Health Policy Reference Centre; MEDLINE; PsycARTICLES; PsycINFO; and SocINDEX. Review methods: PRISMA guidelines were followed in the conduct and reporting of this review. All included studies were critically appraised using the Critical Appraisal Skills Program tools. Meta-ethnographic techniques were used to integrate findings from the qualitative studies. Given the heterogeneous nature of the quantitative studies, data synthesis was narrative. Results: Seventy research reports met the eligibility criteria: 22 qualitative and 48 quantitative reporting on 4, 816 stroke survivors. The qualitative studies described a contraction of the social network, with non-kin contact being vulnerable. Although family were more robust network members, significant strain was observed within the family unit. In the quantitative studies, poor functional social support was associated with depression (13/14 studies), reduced quality of life (6/6 studies) and worse physical recovery (2/2 studies). Reduced social network was associated with depression (7/8 studies), severity of disability (2/2 studies) and aphasia (2/2 studies). Although most indicators of social network reduced post stroke (for example, contact with friends, 5/5 studies), the perception of feeling supported remained relatively stable (4/4 studies). Conclusion: Following a stroke non-kin contact is vulnerable, strain is observed within the family unit, and poor social support is associated with depressive symptoms.